2023
DOI: 10.2196/42325
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Online-Only Blended Cardiopulmonary Resuscitation Training: Static-Group Comparison Study

Abstract: Background Basic life support (BLS) education is essential for improving bystander cardiopulmonary resuscitation (CPR) rates, but the imparting of such education faces obstacles during the outbreak of emerging infectious diseases, such as COVID-19. When face-to-face teaching is limited, distance learning—blended learning (BL) or an online-only model—is encouraged. However, evidence regarding the effect of online-only CPR training is scarce, and comparative studies on classroom-based BL (CBL) are la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The literature also contains some recent studies that have integrated online and virtual CPR training for remote communities. Although the CPR quality results did not differ between online and face-to-face training, and although online training required more days to improve competency, they nevertheless recommended online training as their first choice ( Chong et al, 2023 ; Lin et al, 2021 ). However, online CPR training might be limited by the internet connection and technology support in rural communities; moreover, most participants prefer traditional face-to-face training ( Jaskiewicz & Timler, 2023 ).…”
Section: Discussionmentioning
confidence: 90%
“…The literature also contains some recent studies that have integrated online and virtual CPR training for remote communities. Although the CPR quality results did not differ between online and face-to-face training, and although online training required more days to improve competency, they nevertheless recommended online training as their first choice ( Chong et al, 2023 ; Lin et al, 2021 ). However, online CPR training might be limited by the internet connection and technology support in rural communities; moreover, most participants prefer traditional face-to-face training ( Jaskiewicz & Timler, 2023 ).…”
Section: Discussionmentioning
confidence: 90%
“…These decreases reduced the expenditure, human resources, and time requirements for learners and instructors in CPR training courses [ 21 ]. One study investigated the cost-effectiveness of blended learning for CPR training; the results revealed that blended learning decreased training costs while achieving similar maintenance of CPR skills relative to the traditional method [ 23 ]. However, some researchers have indicated that despite the costs and time reductions offered by blended learning, such learning does not ensure that participants will acquire further professional knowledge and proficiency in a demanding training environment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…BLS training by self-directed remote online-only learning and deliberate practice was reported to be comparable to the conventional classroom-based instructor-led method. 16 …”
Section: Discussionmentioning
confidence: 99%